2016
DOI: 10.1039/c6ra17143e
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic surface-enhanced Raman scattering detection of influenza A virus enhanced by two-dimensional gold@silver core–shell nanoparticle arrays

Abstract: A surface enhanced Raman scattering (SERS) based biosensor using a direct immunoassay platform was demonstrated for influenza A detection. The sensitivity was improved ~4 times by using a well-tuned Au@Ag 2D array instead of a flat Au film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Surface-enhanced Raman scattering (SERS)-based immunoassay has attracted much attention as an ultrasensitive detection method for analytes in biological samples. [1][2][3][4] The extrinsic SERS immunoassay is the platform for detecting target antigens using metal nanoparticles (MNPs), such as gold nanoparticles (AuNPs), 5 gold nanostars, 2 and their aggregates, 6 labelled with a Raman reporter molecule and the detection antibody, which are called 'SERS probes'. 7 The Raman scattering efficiency of the reporter molecule is signicantly enhanced by the strong electromagnetic eld near the MNP surface when the localized surface plasmon is excited by the incident laser light.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface-enhanced Raman scattering (SERS)-based immunoassay has attracted much attention as an ultrasensitive detection method for analytes in biological samples. [1][2][3][4] The extrinsic SERS immunoassay is the platform for detecting target antigens using metal nanoparticles (MNPs), such as gold nanoparticles (AuNPs), 5 gold nanostars, 2 and their aggregates, 6 labelled with a Raman reporter molecule and the detection antibody, which are called 'SERS probes'. 7 The Raman scattering efficiency of the reporter molecule is signicantly enhanced by the strong electromagnetic eld near the MNP surface when the localized surface plasmon is excited by the incident laser light.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity can be improved further by performing the immunoassay on SERS-active substrates, such as two-dimensional (2D) arrays of gold nanotriangle, 2 gold nanostar, 11 gold nanosphere, 12 and gold core-silver shell (Au@Ag) nanoparticles (NPs) 4 formed on solid substrates. Many research groups reported a variety of combinations of the SERS probe and SERS-active substrate, demonstrating the ultrasensitive detection of analytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study two-dimensional (2D) coreeshell structure of (Au@Ag) NPs arrays was used as substrate for SERS based biosensor [64]. In this report, the target molecule was influenza A virus, being obtained a LOD of 6 TCID50/mL and a linear range between 5 and 56 TCID50/mL using a unique SERS substrate (well-tuned Au@Ag 2D array) ( Fig.…”
Section: Silver Nanoparticles (Agnps)mentioning
confidence: 82%
“…Design of a modified electrode with two-dimensional (2D) coreeshell structure of (Au@Ag) NPs array as substrate. This figure was obtained with permission from Ref [64]…”
mentioning
confidence: 99%